M. Santucci Cutaneous T-cell lymphomas: histology (Hematology Meeting Reports, 2009)
Primary cutaneous lymphomas often have a different clinical behaviour and prognosis from histologically similar systemic lymphomas involving the skin secondarily, and therefore require different types of therapies. For that reason, recent classification systems such as the EORTC classification for primary cutaneous lymphomas1 and the WHO classification for tumours of haematopoietic and lymphoid tissues2 considered primary cutaneous lymphomas as separate entities. Although there was consensus between the EORTC and WHO schemes on the classification of most types of primary cutaneous T-cell lymphomas (CTCLs), remaining differences between the two classification systems resulted in considerable debate and confusion.